Deletion of the ATP2 Gene in Candida albicans Blocks Its Escape From Macrophage Clearance - Zhang, Yishan; Tang, Chuanyan; Zhang, Zhanpeng; Li, Shuixiu; Zhao, Yajing; Weng, Luobei; Zhang, Hong (Frontiers in Cellular and Infection Microbiology, 2021)
Macrophages provide the first-line defense against invasive fungal infections and, therefore, escape from macrophage becomes the basis for the establishment of Candida albicans invasive infection. Here, we found that deletion of ATP2 (atp2Δ/Δ) in C. albicans resulted in a dramatic decrease from 69.2% (WT) to 1.2% in the escape rate in vitro. The effect of ATP2 on macrophage clearance stands out among the genes currently known to affect clearance. In the normal mice, the atp2Δ/Δ cells were undetectable in major organs 72 h after systemic infection, while WT cells persisted in vivo. However, in the macrophage-depleted mice, atp2Δ/Δ could persist for 72 h at an amount comparable to that at 24 h. Regarding the mechanism, WT cells sustained growth and switched to hyphal form, which was more conducive to escape from macrophages, in media that mimic the glucose-deficient environment in macrophages. In contrast, atp2Δ/Δ cells can remained viable but were unable to complete morphogenesis in these media, resulting in them being trapped within macrophages in the yeast form. Meanwhile, atp2Δ/Δ cells were killed by oxidative stress in alternative carbon sources by 2- to 3-fold more than WT cells. Taken together, ATP2 deletion prevents C. albicans from escaping macrophage clearance, and therefore ATP2 has a functional basis as a drug target that interferes with macrophage clearance.